Mapeamento de competências na ciência da informação: uma análise à luz da produção científica - Neves Filho, Salomão (2024)
Competency mapping is a tool capable of identifying knowledge, skills and attitudes necessary to carry out activities in any organizational segment. In the scope of Information Science, the performance of information professionals must be aligned with the demands of contemporary society, and it is essential to identify the skills of these professionals today. In this context, the research aims to analyze scientific production on mapping skills within the scope of Information Science based on bibliometric indicators. Regarding methodological procedures, the research is classified as exploratory and descriptive, supported by a bibliometric analysis. It used a quantitative approach to describe and analyze bibliometric production and linkage indicators. 11 works were researched, six master's theses and five scientific articles from 2014 to 2023, extracted from three databases: Capes Theses and Dissertations Catalog, Capes Periodicals Portal and BRAPCI. Different areas of activity were identified for mapping skills in the context of Information Science, such as libraries, archives, teaching and industry, corroborating the heterogeneity that characterizes the area. Three processes related to skills mapping were also identified, namely: library management, information management and knowledge management, suggesting that the information professional is capable of developing different activities linked to information and strongly marked by the use of information technologies. and communication, which requires the development of individual, professional, informational skills and mastery of technologies that meet the needs of the different contexts in which they can operate. The co-citation network pointed out that there are authors who strongly reference research on management and skills mapping, but who do not belong to the IS area, suggesting that skills mapping reveals itself as a field to be explored by IS authors. The research also revealed that competency mapping does not have a single guideline for its development, with models or instruments validated in other studies being used, as well as own instruments being created to guide the mapping of competencies in informational units.